Beyond environmental monitoring: Are automatic time-lapse cameras efficient tools for temperature measurement in remote regions? - Grenier, Jérémy; Decaulne, Armelle; Bhiry, Najat (Géomorphologie : relief, processus, environnement, 2024)
Automatic time-lapse cameras are frequently used to monitor snow height as well as snow and ice related processes occurring on slopes in cold regions because of the many advantages they bring to researchers. In addition to providing important visual information’s about the dynamic of the studied area, most of these types of cameras are now equipped with thermal sensors able to register temperature data for every picture taken. The instrumentation set up within Tasiapik Valley, near Umiujaq, in Nunavik (northern Québec), enabled us to assess the potential of automatic time-lapse cameras for temperature measurement by comparing data retrieved on photographs from time-lapse cameras with data from two nearby weather stations. Our results indicate that the temperature measurements from the time-lapse cameras from August to the onset of February are relatively accurate while their weaker performances for temperature measurement occurred in late winter and spring (March - June). Moreover, regardless of the year, time-lapse cameras were most accurate in the morning (09:00 AM – 11:00 AM), while in the afternoon (12:00 PM – 3:00 PM), they tended to over-estimate temperatures. Based on our observations and data analyses, this over-estimation of temperatures seems to be caused by external factors such as sky conditions and high values of downwelling shortwave radiation lasting from February to June at our study site. The local environment surrounding the cameras might also affect the performances of time-lapse cameras at temperature measurement. Les appareils photographiques automatisés sont fréquemment utilisés pour surveiller la hauteur de neige ainsi que les processus liés à la neige et à la glace qui se produisent sur les pentes de régions froides en raison des nombreux avantages qu’ils apportent aux chercheurs. En plus de prodiguer d’importantes informations visuelles sur la dynamique du site à l’étude, la plupart des modèles d’appareil photographique automatisé est désormais doté de capteurs thermiques permettant ...